2022
DOI: 10.1186/s12884-022-04460-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of malnutrition during adolescent pregnancy in southern Ethiopia: a community-based study

Abstract: Background Adolescent pregnancy is a major public health problem with significant medical, nutritional, social and economic risk for mothers and their infants. The purpose of this study was to determine prevalence and predictors of malnutrition among pregnant adolescents in Kore district, southern Ethiopia. Methods Data were obtained from randomly selected consenting four hundred twenty five pregnant adolescents on March 2018 using interviewer-admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
1
4
1
Order By: Relevance
“…Based on this, one-fourth, 25.6% (95% CI: 24.5–26.9), of AGYW in Ethiopia had undernourished. This is in line with the research report 26.4% conducted in southern Ethiopia [ 37 ]. This finding is higher than studies conducted in Gondar, Ethiopia in which 14.4% were undernourished [ 9 ].…”
Section: Discussionsupporting
confidence: 92%
“…Based on this, one-fourth, 25.6% (95% CI: 24.5–26.9), of AGYW in Ethiopia had undernourished. This is in line with the research report 26.4% conducted in southern Ethiopia [ 37 ]. This finding is higher than studies conducted in Gondar, Ethiopia in which 14.4% were undernourished [ 9 ].…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, the findings revealed that the prevalence of undernutrition in Gondar is 61.3%. This figure is higher than the findings of other studies, which have reported a prevalence of 26.4% in southern Ethiopia ( 28 ) and 14.4% in Gondar ( 9 ). A possible reason for this difference might be the differences in study population, period, and sample size.…”
Section: Discussioncontrasting
confidence: 78%
“…Further research into undernutrition related to older children and adolescents is crucial as the drivers of poor nutrition and ultimately interventions to address this issue differ in this population compared to the U5 children. Adolescents in particular have more choice of what they eat ( 27 ) and many may have their own families to feed ( 28 ). A multidisciplinary approach to addressing this burden is necessary along with greater global investment ( 4 ).…”
Section: Discussionmentioning
confidence: 99%